Testing the effectiveness of environmental DNA (eDNA) to quantify larval amphibian abundance. Issue 6 (27th June 2022) - Breton, Brie‐Anne A.; Beaty, Lynne; Bennett, Amanda M.; Kyle, Christopher J.; Lesbarrères, David; Vilaça, Sibelle Torres; Wikston, Madison J. H.; Wilson, Chris C.; Murray, Dennis L.
Abstract: Environmental DNA (eDNA) monitoring is rapidly becoming an established approach for detecting the presence of aquatic organisms and may also be useful for indexing or estimating species abundance. However, the link between eDNA concentration and abundance of individuals (i.e., density or biomass) remains tenuous and may vary widely across species and environmental conditions. We investigated the relationship between eDNA concentration and abundance in two common and closely related amphibians in eastern North America, the wood frog ( Rana sylvatica ), and northern leopard frog ( R. pipiens ). We manipulated tadpole density in 80‐L mesocosms and documented the relationship between tadpole density and biomass and eDNA concentration through time. The two species differed in the amount of detectible genetic material produced, despite having comparable biomass. Concentration of eDNA increased with tadpole numbers and was primarily correlated with tadpole density in wood frogs and biomass in leopard frogs. eDNA degradation rates were rapid and comparable between species, with tadpoles becoming indetectable within 5 days post‐removal from the mesocosm, irrespective of tadpole density. Overall, our findings support that eDNA concentration has potential for tracking amphibian abundance in wetlands, but that indices of abundance are likely to be coarse and species‐specific calibration will be required. Future research should address how biotic and abiotic factors influence eDNA production, degradation, and recovery across species and through time before relying on eDNA for monitoring amphibian abundance in nature. Abstract : We evaluated the reliability of eDNA for determining the abundance of tadpoles of two closely‐related and widely‐distributed amphibian species from North America. Using mesocosms experiments, we showed that eDNA concentrations from the two species were related to abundance metrics and had comparable rates of eDNA degradation, but differed in the amount of genetic material produced as well as the relationship between eDNA and biomass vs. density.